PENGARUH KOMPETENSI TUTOR TERHADAP HASIL BELAJAR SISWA PAKET B DI SPNF SKB KABUPATEN LAHAT - Ramadhanti, Trias; Helmi, Henny; Saputra, Ardi; Shomedran (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study is motivated by the suboptimal learning outcomes of Package B students at SPNF SKB Kabupaten Lahat, as indicated by an average score of 78.6. The main problem addressed is whether tutor competence influences students’ learning outcomes. This research aims to determine the extent of the influence of tutor competence, which includes pedagogical, personal, social, and professional competencies, on the learning outcomes of Package B students. This study employed a quantitative approach with a descriptive method. The population consisted of 98 students, all of whom were selected as the sample using a total sampling technique. Data were collected through questionnaires, observation, and documentation. The research instrument was tested for validity and reliability, with all items declared valid and a Cronbach’s Alpha value of 0.963, indicating high reliability. Data analysis was conducted using percentage analysis and simple linear regression to test the hypothesis. The results showed that tutor competence was generally in the “fairly good” category across all aspects, particularly pedagogical competence with a percentage of 57.9%. Statistical testing revealed that tutor competence has a positive and significant effect on students’ learning outcomes. This indicates that higher tutor competence leads to improved learning outcomes among Package B students. In conclusion, tutor competence is an important factor influencing the success of learning in nonformal education. Therefore, efforts to improve tutor competence are necessary to enhance students’ learning outcomes.